Cell Phone Tower Radiations And Associated Health Hazards In Hilla City, Babylon, Iraq (Advances in Applied Biological Research, 2026)
Background: The obvious increase in mobile phone base stations in Iraq after the  year 2003 has raised worries about potential nonspecific health symptoms affected  by electromagnetic radiation produced. Studies on this issue in Iraq were scarce.  Objective of the study: To identify the possible nonspecific health problems  among adult inhabitants who lived for five years or more at a distance of up to  300 meters from mobile phone base stations and towers compared to those who  lived far away from cell phone towers (500 meters and more). Methods: A cross sectional descriptive study was conducted in Hilla city, Babylon province, during  the period from November 2017 through February 2018. A non-probability  (purposive sample) was selected from populations living in AL-Hilla urban  regions for more than five years close to four randomly selected base station towers  and those who lived in areas more than 500 meters from the same cell towers. A  convenience sample constituted 278 adults aged 18 years and above of both sexes  who were investigated after obtaining their verbal consent and who had completed  a pretested questionnaire that focused on the subjective symptoms they suffered  from via in-depth face-to-face interviews. Results: The findings of the current  study revealed a statistically significant increase in ill-health effects (prevalence  of nonspecific symptoms)
Keywords: Mobile Phone Tower; Health Hazards; Hilla City - Iraq